Robotic versus open component separation: A retrospective cohort and propensity score analysis of complication rates and clinical outcomes - Silvana Maldonado; Carlos Gonzales; Anshumi Desai; Jiddu Guart; Alba Zevallos Ventura; Bryan Valcarcel; Joseph Escandon; Natalia Mejia; Camila Franco Mesa; J. Smith Torres Roman; Hamed Sarikhani; Jose Luis Barrueto; et al. (PLoS ONE, 2026)
Background Complex ventral hernias are a surgical challenge associated with high morbidity and healthcare costs. Component separation techniques have improved throughout the years with better outcomes, although the optimal approach remains debated. Robotic surgery has shown promising outcomes as an alternative to open repair, although data in large multicenter studies is still limited. Methods A retrospective cohort study was conducted using the American College of Surgeons National Surgical Quality Improvement Program (ACS-NSQIP) database. Adult patients undergoing component separation for ventral hernia repair were identified using CPT and ICD codes. Outcomes included 30-day surgical, wound, medical, and overall complications, as well as length of stay and readmission. Multivariable logistic regression and propensity score matching were applied to adjust for baseline differences. Results A total of 6,207 patients were included, from those 4,443 (71.6%) underwent open technique and 1,764 (28.4%) robotic. After propensity matching (n = 5,259), robotic repair was independently associated with significantly lower overall complication rates (4.8% vs. 19.6%, aOR 0.193, 95% CI 0.140–0.265, p < 0.001), including wound (2.2% vs. 10.2%, aOR 0.164, p < 0.001), surgical (2.9% vs. 10.0%, aOR 0.271, p < 0.001), and medical complications (2.0% vs. 7.0%, aOR 0.229, p < 0.001). Robotic surgery was also associated with shorter length of stay (1.34 vs. 3.86 days, p < 0.001) and lower readmission rates (4.4% vs. 9.1%, p < 0.001). Conclusions Robotic component separation for ventral hernia repair is associated with lower postoperative complication rates, shorter length of stay, and fewer readmissions compared to the open approach. These benefits remained significant after multivariate analysis and propensity score matching, supporting the robotic technique as an effective strategy. Prospective studies are warranted to evaluate long-term outcomes, including recurrence, and to assess cost-effectiveness to optimize evidence-based surgical decision-making.